PENGENDALIAN DIRI ANAK JALANAN DI LAMPU LALU LINTAS MALL SKA PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to describe the characteristics of street children and to determine self-control of street children at the Traffic Lights at SKA Mall Pekanbaru. This type of research is a descriptive study with a qualitative approach. Sources of data in this study were 5 street children at the Traffic Lights SKA Mall Pekanbaru. Data collection techniques are interviews, observation and documentation, using structured interview guidelines, observation guidelines and documentation. Data analysis techniques are data reduction, data presentation and drawing conclusions or verification. The results obtained from the characteristic research are street children aged 9-13 years, predominantly boys. Most of the street children in the area drop out or don't go to school, working 6-10 hours a day. Still have a close relationship with parents, and live with parents. Overall street children already have good self-control. But there is still a little deviant behavior on the streets.Key Words: Street Children, Characteristics, Self-Control